Astronomical Validation of the Computational Unified Field Theory (CUFT) Critical Prediction (Global Journal of Science Frontier Research, 2019)
Twenty-first Century Physics has reached a pivotal point calling for a Paradigmatic Shift from the Old Material- Causal Paradigm underlying Relativity Theory RT and Quantum Mechanics QM to the New A-Causal Computation ACC Paradigm of the Computational Unified Field Theory CUFT which was shown capable of resolving the theoretical inconsistency between RT QM and discard darkmatter and dark-energy as superfluous non-existent In order to satisfy Kuhn s well known criteria for such a Paradigmatic Shift it is necessary to empirically validate at least one unique critical prediction of the CUFT which differentiates it from the predictions of both RT and QM Initial empirical validation was given through the findings of the Proton-Radius Puzzle and two additional direct critical-predictions of the CUFT are outlined and called for empirical validation Based on the New ACC Paradigm s discovered singular higher-ordered Universal Computational Consciousness Principle s UCP Collective Human Consciousness Focus CHCF postulate a unique prediction regarding the Collective Human Consciousness Focus Non-Continuous Universal Expansion Rate Hypothesis CHCF-NCUERH at the Jewish Rosh-Hashanna New Year is called for This new CHCF-NCUERH critical-prediction also offers a possible resolution of the Universe s Accelerated Expansion Rate Enigma The far reaching theoretical implications which would ensue from an empirical validation of one of the CUFT s critical predictions is discussed which includes a challenging of the Big-Bang Model negation of dark-matter and darkenergy revision of RT s and QM s basic Material-Causal assumption full integration of the four basic physical features of space energy mass and time etc